Bioinspired Multifunctional Cellular Plastics with a Negative Poisson's Ratio for High Energy Dissipation. Issue 33 (9th July 2020) - Li, Dewen; Bu, Xiaochen; Xu, Zongpu; Luo, Yingwu; Bai, Hao
Abstract: Cellular plastics have been widely used in transportation, aerospace, and personal safety applications owing to their excellent mechanical, thermal, and acoustic properties. It is highly desirable to impart them with a complex porous structure and composition distribution to obtain specific functionality for various engineering applications, which is challenging with conventional foaming technologies. Herein, it is demonstrated that this can be achieved through the controlled freezing process of a monomer/water emulsion, followed by cryopolymerization and room temperature thawing. As ice is used as a template, this method is environmentally friendly and capable of producing cellular plastics with various microstructures by harnessing the numerous morphologies of ice crystals. In particular, a cellular plastic with a radially aligned structure shows a negative Poisson's ratio under compression. The rigid plastic shows a much higher energy dissipation capability compared to other materials with similar negative Poisson's ratios. Additionally, the simplicity and scalability of this approach provides new possibilities for fabricating high‐performance cellular plastics with well‐defined porous structures and composition distributions. Abstract : Cellular plastics with complex porous structure and composition distribution are in great demand for various engineering applications, yet are challenging to realize through conventional foaming technologies. An ice‐templating approach, involving a controlled freezing process of a monomer/water emulsion, followed by cryopolymerization and room‐temperature thawing, is developed to fabricate such cellular plastics in a scalable and environmentally friendly manner.